Diversity of Bamboo Species (Poaceae: Bambusoideae) in The Bukit Kinai Area, Bengkayang Regency - Jeno Jeno; Rafdinal Rafdinal; Dwi Gusmalawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Bamboos are one of the plant species that make up forest vegetation that has many benefits both economically, ecologically and socio-culturally. Environmental quality can be assessed using data on the diversity of bamboo species. This study aims to determine the composition and level of diversity of bamboo species in the Bukit Kinai region. Determination of sampling locations using purposive sampling method with double plots. This research was conducted in January-April 2023 in the Bukit Kinai area of Setanduk Village, Capkala District, Bengkayang Regency. Seven bamboo species from four different genera were identified, namely Bambusa vulgaris Schrad Ex. JC Wendl, Dendrocalamus asper (Schult. F) Backer, Gigantochloa hasskarliana (Kurz) Backer, Schizostachyum blumei Nees, S. brachyladum (Kurz ex Munro) Kurz, S. lima (Blanco) Merrill, and S. mampouw Widjaja. The highest Frequency, Density and INP values were found in the species Gigantochloa hasskarliana (Kurz) Backer, which were 0.85, 261.25 clumps/ha, and 110%, respectively. Low species richness (R = 1.059), low species diversity (H = 0.917), and moderate species evenness and species dominance (E = 0.471 and C = 0.555) were observed in the Bukit Kinai region. Based on this study, the bamboo community in the Bukit Kinai area was in an unstable condition so that its environmental quality can be categorized as poor.